2017
DOI: 10.1080/00498254.2016.1261307
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, excretion and pharmacokinetics of [14C]glasdegib (PF-04449913) in healthy volunteers following oral administration

Abstract: 1. The metabolism, excretion and pharmacokinetics of glasdegib (PF-04449913) were investigated following administration of a single oral dose of 100 mg/100 μCi [C]glasdegib to six healthy male volunteers (NCT02110342). 2. The peak concentrations of glasdegib (890.3 ng/mL) and total radioactivity (1043 ngEq/mL) occurred in plasma at 0.75 hours post-dose. The AUC were 8469 ng.h/mL and 12,230 ngEq.h/mL respectively, for glasdegib and total radioactivity. 3. Mean recovery of [C]glasdegib-related radioactivity in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…A human mass balance study showed glasdegib to be metabolised primarily by hepatic CYP3A4, and to a lesser extent, by uridine diphosphoglucuronosyltransferase 1A9 . The involvement of CYP3A4 in the glasdegib metabolism was supported by the result of the previous DDI study, in which a known strong inhibitor of CYP3A, ketoconazole, increased glasdegib AUC inf and C max by 140% and 40%, respectively, in healthy volunteers .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A human mass balance study showed glasdegib to be metabolised primarily by hepatic CYP3A4, and to a lesser extent, by uridine diphosphoglucuronosyltransferase 1A9 . The involvement of CYP3A4 in the glasdegib metabolism was supported by the result of the previous DDI study, in which a known strong inhibitor of CYP3A, ketoconazole, increased glasdegib AUC inf and C max by 140% and 40%, respectively, in healthy volunteers .…”
Section: Discussionmentioning
confidence: 84%
“…The total study duration was approximately 17 days. Glasdegib 100 mg once daily is the clinical dosage of glasdegib that is under evaluation in Phase 2/3 trials, and was selected based on clinical activity, biomarker modulation, safety and tolerability data from previous studies in patients with haematologic malignancies and healthy volunteers .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the ADME study also indicated that glasdegib major route of elimination is primarily through CYP3A4 oxidation, and that contribution from the glucuronidation pathway via the uridine 5′‐diphospho‐glucuronosyltransferase 1‐9 (UGT1A9) is only minor . In that study, 4.2% of the administered dose was found in the urine as N‐glucuronide metabolite but not in the feces, whereas 19.5% of the administered glasdegib parent dose was recovered in the feces.…”
Section: Discussionmentioning
confidence: 88%